Motivos de uso y no uso de puentes peatonales en la Ciudad de México: la perspectiva de los peatones - Elisa; Julio; Jorge; Chias; Héctor; Sánchez-Restrepo, H. (Salud Pública de México, 2010)
Objective. To analyze the motives for using and not using pedestrian bridges (PB). Material and Methods. A crosssectional survey was conducted of a sample of pedestrian users and non-users of PB; a logistic regression model was used to analyze the motives for use and non-use. Results. The prevalence of non-use was 50.5 % of 813 surveyed pedestrians; the principal reason to use a PB was safety, and not to use it was “laziness”. There were significant differences when analyzing the reason of non-use in the age groups 19 to 36 years, adjusted for education and physical characteristics of the PB ([aOR=1.7; 95 % CI=1.06-2.86] and [ORa.1.9; 95% CI=1.14-3.33], respectively). Conclusions. The results of this study allow us to identify important aspects to consider –from the perspective of the pedestrians– when constructing new PB and improving existing PB to increase use in areas with a high risk of pedestrian injuries.